Melayani Dengan Kasih , Berkarya Bagi Masyarakat Dampak Penginjilan Terhadap Pertumbuhan Rohani Kristen Dalam Kaum Jemaat HKBP Pangururan - Bangun, Bangun; Damanik, Putri; Gajah, Pergaulan; Butarbutar, Parni; Siregar, Riden Syamsul Bahri (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2026)
This community service activity aims to improve the spiritual growth of the congregation, especially youth at HKBP Pangururan, in facing the challenges of the digital 5.0 era which significantly influence behavior, mindset, and spiritual life of Generation Z and Alpha. The main problems identified include declining interest in worship, low participation in spiritual activities, and imbalance between digital life and spiritual values. The method used was a participatory approach consisting of preparation, implementation, and evaluation stages. The activities included Sunday services, Sunday school teaching, Bible study sessions, home and hospital visits, and youth retreats. Evaluation was conducted through questionnaires distributed to the congregation to measure the impact of the program. The results showed an increase in awareness and participation of the congregation, especially youth, in spiritual activities, as indicated by higher attendance in worship services and increased motivation to read the Bible and pray. Additionally, the program contributed to enhancing parental awareness in guiding their children to balance technology use and spiritual life. In conclusion, community service based on spiritual ministry is effective in strengthening the spiritual quality of the congregation and should be sustained to support continuous faith development.